N-Heterocyclic Carbene Catalyzed Transesterification of Polytrifluoroethyl Acrylates - Hepperle, Johannes A. M.; Samanta, Ramesh C.; Studer, Armido (Synlett, 2013)
This article describes N-heterocyclic carbene catalyzed transesterification of polytrifluoroethyl acrylates which are readily prepared by nitroxide-mediated radical polymerization using a sterically hindered alkoxyamine as an initiator/regulator. Controlled radical polymerization provides polytrifluoroethyl acrylates with molecular weights (Mn) ranging from 1600 to 17200 g/mol and low molecular weight distributions (polydispersity index, PDI = 1.1–1.2). The polytrifluoroethyl acrylates are readily transesterified with various alcohols in the presence of an NHC catalyst.
Keywords: nitroxide-mediated radical polymerization; N-heterocyclic carbenes; esterification; polyacrylates; polymer analogous reaction